دور عضو الهيئة التدريسية في تطوير العملية التعليمية وانعكاساته على جودة التعليم العالي " دراسة ميدانية لرصد آراء أعضاء الهيئة التدريسية في جامعة تشرين" - محمد, محمود علي; حسن, ميسون حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى تعرف درجة مساهمة أعضاء الهيئة التدريسية بجامعة تشرين في تطوير العملية التعليمية, وبناء وتطوير المناهج الجامعية, والعلاقة مع الطلاب والتفاعل معهم, بالإضافة إلى دراسة الفروق بين أعضاء الهيئة التدريسية في درجة مساهمتهم في تطوير العملية التعليمية تبعاً لمتغيرات الجنس, والكلية, والمرتبة العلمية. اعتمدت الباحثة على المنهج الوصفي التحليلي, وتمّ تصميم استبانة وزعت على /251/ من أعضاء هيئة التدريس, وبعد الدراسة والتحليل توصل البحث إلى النتائج الآتية: 1- يعمل عضو هيئة التدريس على بناء منهج متعدد الحقول المعرفية مستفيداً من المعايير العالمية لتقويم المناهج والمواد الدراسية, ومراعياً التكامل بين الجوانب المعرفية والمهارية والوجدانية. 2- تتسم علاقة عضو هيئة التدريس مع طلابه بأنها علاقة جيدة, حيث يعمل معهم بروح الفريق، ويوزع الأدوار المطلوبة من كل طالب، ويحترم قراراتهم واتجاهاتهم ويوجهها الوجهة السليمة. 3- يعتمد عضو هيئة التدريس العدل والموضوعية في تقدير الدرجات ويراعي الفروق الفردية بين الطلاب. 4- لا يختلف أعضاء الهيئة التدريسية في درجة مساهمتهم بتطوير العملية التعليمية والمناهج والقدرة على التفاعل مع الطلاب باختلاف الجنس والتخصص والمرتبة العلمية. The current research aims to know the degree of contribution of faculty members at the University of Tishreen in the development of the educational process, and to build and develop university curricula and the relationship with the students and interact with them, in addition to studying the differences between faculty members in the degree of their contribution to the development of the educational process due to sex, and college, and scientific level. Researcher relied on descriptive analytical method, the questionnaire was designed and distributed to the / 251 / of faculty members, and after the study and analysis of research found the following results: The faculty member to build a multi-disciplinary approach, taking advantage of global standards to evaluate the curriculum and teaching materials, and taking into account the integration of the knowledge and skills aspects and compassionate. Characterized faculty member relationship with his students as a good relationship, where he works with a team spirit and distributes roles required of each student and respects their decisions and their attitudes and destination-driven sound. depends faculty member objective and fair assessment grades and takes into account individual differences among students. no different faculty members in the degree of their contribution to the development of the educational process and the curriculum and the ability to interact with students, depending on their gender and scientific specialization and rank.